Experimental and numerical investigation on the rheological behaviour of bituminous composites via DSR testing. (1st June 2021) - Ziade, Elio; Fakhari Tehrani, Fateh; Beghin, Alain; Petit, Christophe; Absi, Joseph; Millien, Anne; Reynaud, Philippe
Abstract : Mastic and mortar are two bituminous composites which play a fundamental role in defining bituminous mixes' properties. Therefore, the main purpose of this paper is to study the behaviour of these materials according to time and frequency with three different approaches: Experimental, analytical, and numerical. To characterise bitumen, mastic, and mortar, a Dynamic Oscillatory Test was carried out on bituminous composites using DSR. Numerically, mortar mechanical properties were assessed by applying a heterogeneous ﬁnite element (FE) modelling. Analytical methods such as Generalised self-consistent schemes (GSCS) and Shift-Homothety-Shift and time Shift (SHStS) have succeeded in predicting mastic and mortar properties. Numerical simulation presented a virtual DSR test able to examine stress and strain distribution in the digital model's microstructure. Since studying the response of the internal structure to an applied stress or strain is complicated using other methods. Thus, aiming to optimise the material formula and improve its mechanical properties. GRAPHICAL ABSTRACT: UF0001